Repositioning fertilizer manufacturing subsidies for improving food security and reducing greenhouse gas emissions in China - Zongyi Wu; Xiaolong Feng; Yumei Zhang; Shenggen Fan (Journal of Integrative Agriculture, 2024)
China removed fertilizer manufacturing subsidies from 2015 to 2018 to bolster market-oriented reforms and foster environmentally sustainable practices. However, the impact of this policy reform on food security and the environment remains inadequately evaluated. Moreover, although green and low-carbon technologies offer environmental advantages, their widespread adoption is hindered by prohibitively high costs. This study analyzes the impact of removing fertilizer manufacturing subsidies and explores the potential feasibility of redirecting fertilizer manufacturing subsidies to invest in the diffusion of these technologies. Utilizing the China Agricultural University Agri-food Systems model, we analyzed the potential for achieving mutually beneficial outcomes regarding food security and environmental sustainability. The findings indicate that removing fertilizer manufacturing subsidies has reduced greenhouse gas (GHG) emissions from agricultural activities by 3.88 million metric tons, with minimal impact on food production. Redirecting fertilizer manufacturing subsidies to invest in green and low-carbon technologies, including slow and controlled-release fertilizer, organic–inorganic compound fertilizers, and machine deep placement of fertilizer, emerges as a strategy to concurrently curtail GHG emissions, ensure food security, and secure robust economic returns. Finally, we propose a comprehensive set of government interventions, including subsidies, field guidance, and improved extension systems, to promote the widespread adoption of these technologies.